2022
DOI: 10.4414/smw.2022.w30217
|View full text |Cite
|
Sign up to set email alerts
|

ORCHID (Outcome Registry for CHIldren with severe congenital heart Disease) a Swiss, nationwide, prospective, population-based, neurodevelopmental paediatric patient registry: framework, regulations and implementation

Abstract: INTRODUCTION: Congenital heart disease (CHD) is the most frequent birth defect. As survival has significantly improved, attention has turned to neurodevelopmental outcomes of children undergoing heart surgery in early infancy. Since multiple risk factors contribute to neurodevelopmental alterations, a nationwide registry collecting data on medical characteristics, interventions, clinical course and neurodevelopment until school-age is needed to improve the quality of management, identify risk- and protective f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Regarding neurological outcomes, most of our patients showed a normal to mildly impaired neurodevelopmental cognitive outcome, and severe neurodevelopmental impairment was an exception. Our findings regarding neurological outcomes are comparable with the results of other research groups as well as the results of our own research group "Heart and Brain" [38,39].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding neurological outcomes, most of our patients showed a normal to mildly impaired neurodevelopmental cognitive outcome, and severe neurodevelopmental impairment was an exception. Our findings regarding neurological outcomes are comparable with the results of other research groups as well as the results of our own research group "Heart and Brain" [38,39].…”
Section: Discussionsupporting
confidence: 91%
“…Full‐text screening of these 193 publications resulted in 35 publications being included in this review. 9 , 13 , 14 , 15 , 16 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 The stages of the search and screening process and reasons for exclusion are presented in the PRISMA‐ScR flow diagram (Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The 35 publications included in the scoping review comprised 33 different studies. Of these, 21 studies examined the implementation of specific programmes or care pathways for neurodevelopmental follow‐up care, 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 42 , 44 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 56 and 12 studies reported on surveys or overviews of current clinical practices in neurodevelopmental follow‐up. 9 , 13 , 14 , 15 , 16 , 30 , 37 , 41 , 43 , 45 , 46 , 55 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations